E-Content Technologies and Perspectives for the European Market - Bruck, Peter A.; Buchholz, Andrea; Karssen, Zeger; Zerfass, Ansgar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Technologies develop rapidly and reach hurricane levels of velocity but quality E-Content and innovative applications lag behind. This book addresses the question how content industries change within a digital environment and what role information and communication technologies play in transforming the competitive landscape. The authors argue that post-industrial societies tend to pay substantial amounts for equipment and gadgets but invest far too little in the quality of the content. As a result, much effort is and has to be spent on the enhancement of E-Content. The contributions give an elaborate overview of: - the specifics, challenges and prospects of content in the network economy; - market developments of digital media services; - paid content business models; - impacts on scientific publishing; - developments in the field of E-Learning; - the interplay between technology and content with the example of interactive digital TV; - the mobile games market; - emerging new cross media markets; - the need to enhance the usability of websites and mobile applications; - how digital applications might be used to capture and store our personal experiences. A final chapter shows the prospects of the European E-Content market and gives an overview of valuable initiatives and resources dealing with the topic of E-Content.
E-Content in Europe: Dimensions of an Emerging Field -- E-Content Market in Europe An Overview -- The State of Digital Media Service Business -- Paid Content: From Free to Fee -- Content Applications: Selected Cases -- The Impact of E-Learning -- Scientific Publishing: A European Strength -- Mobile Games: An Emerging Content Business Area -- Cross-Media on the Advance -- User-Centric Content Production and Interaction -- Interactive Digital Television in Europe -- The Usability Factor: Improving the Quality of E-Content -- Experience Machines: Capturing and Retrieving Personal Content -- Outlook -- Prospects of E-Content in Europe -- A Guide to European Initiatives and Resources in E-Content.
Keywords: Industrial management; Management; Media Management; Innovation/Technology Management